An in-depth case study of a modular service delivery system in a logistics context. Issue 3 (30th April 2021) - Ponsignon, Frédéric; Davies, Phil; Smart, Andi; Maull, Roger
Abstract : Purpose: The objective of this work is to empirically investigate the design of a service delivery system that supports the provision of modular service logistics offerings. Design/methodology/approach: An in-depth single-case study relying on interview data and extensive documentary evidence is carried out in the business-to-business (B2B) logistics sector. Three main analytical techniques are used to make sense of the qualitative data: thematic analysis, process mapping and the application of modular operators. Findings: A modular service delivery system comprises three types of processes that collectively deliver modular offerings. The platform consists of core processes that enable the collection, transport and delivery of physical items for all offerings (modular and non-modular). Dedicated modular processes are mandatory and exclusive to individual modular offerings. Optional modular processes are shared across several modular offerings. Interfaces regulate physical (e.g. parcels or parts) and information (e.g. booking data) inputs provided by the customer in order to control the interdependencies within these different process types. Practical implications: The identification of three process types and their interdependencies provides detailed insights into how managers can design modular logistics services that benefit from economies of scale and meet increasingly variable customer requirements. The importance of well-designed interfaces among the customers, the service offering and the service delivery system is highlighted. Originality/value: This study extends previous modularity studies in service logistics. It is the first study to apply modular operators to determine the presence of modularity in the service delivery system and to establish the role of different process types in enabling modularity in the service delivery system.